2013
DOI: 10.1159/000356217
|View full text |Cite
|
Sign up to set email alerts
|

Visit-To-Visit Variability in Systolic Blood Pressure Is a Novel Risk Factor for the Growth of Intracranial Aneurysms

Abstract: Background: Although rupture of unruptured intracranial aneurysms (UIAs) is closely associated with UIA growth during follow-up, few studies have investigated how UIAs grow during observation. Hypertension appears to affect the formation of intracranial aneurysms. However, few studies have investigated the association of blood pressure variability with UIA growth. Visit-to-visit variability (VVV) in systolic blood pressure (SBP) is a newly defined concept which appears to be a good predictor of stroke. With th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Table 1 gives an overview of the included patient populations. The mean duration of follow-up for all cohorts combined was 2.8 patient-years (range of mean follow-up per cohort, 1.0-18.9 years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Table 1 gives an overview of the included patient populations. The mean duration of follow-up for all cohorts combined was 2.8 patient-years (range of mean follow-up per cohort, 1.0-18.9 years).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies on 9 unique cohorts of patients were considered high quality according to the Newcastle Ottawa Scale ( Table I in the online-only Data Supplement). 6,9,11,12,14,16,19,20,22,23,25 Table 2 gives an overview of the definitions of aneurysm growth and the type of imaging modalities used to assess aneurysm growth. …”
mentioning
confidence: 99%
“… 27 Along with accompanying reports, 28 , 29 Rothwell et al 27 believed that these findings challenged the usual blood pressure hypothesis and had implications for diagnosis, treatment, and monitoring of patients with hypertension. Igase et al 30 also showed that the clinical significance of SBPV was higher than that of MSBP with regard to the growth of unruptured intracranial aneurysms. In addition, many reports have demonstrated that SBPV was significantly correlated with cardiac damage, renal dysfunction, and stroke.…”
Section: Discussionmentioning
confidence: 97%
“…• Hypertension (defined as systolic blood pressure greater than or equal to 140 mmHg or greater than or equal to 90 mmHg diastolic in adults or systolic or diastolic blood pressure above the 95 percentile in children) (preexisting CDE) [5,8,[11][12][13]. • Tobacco smoking status: (a) never, (b) former (including start and end date of smoking), (c) current (including starting date) and (d) unknown (modified CDE) [1,[9][10][11][12][13][14][15][16][17]. Radiological findings (Table 7).…”
Section: Description Of Core Cdesmentioning
confidence: 99%
“…• Anatomical aneurysm site based on angiography (modified CDE) [5,9,[18][19][20][21][22][23][24][25][26]. • Maximum aneurysm diameter (in mm) in any direction (new CDE) [5,8,9,[16][17][18][19][20][22][23][24][25][26][27][28][29]. • Maximum aneurysm height (in mm) perpendicular to aneurysm neck (new CDE) [30].…”
Section: Description Of Core Cdesmentioning
confidence: 99%